Uji Toksisitas Fraksi Air Impatiens balsamina Pada Tikus Betina Galur Sprague Dawley - Nurqolbiah, Entang; Kusharyanti, Indri; Nurbaeti, Siti Nani (Pharmaceutical Sciences and Research, 2014)
The present study was aimed to predict the level of toxicity of aqueous fraction of Impatiens balsamina by acute toxicity study using OECD guideline 425. Female Sprague Dawley 8-12 week and weight between 140-170 gram were used, the amount of experimental rats were 10 rats. Rats were sequentially administered all the fraction in single dosage (limit test) of 2000 mg/kg body weight and 5000 mg/kg of body weight. All the animals were individually studied for mortality, wellness parameters, food consumption,water consumption, body weight. Histopathological examination was done on the liver and kidney. The result of this study showed that no mortality and no significant changes were observed in wellness parameter, body weight, food consumption, and water consumption at 2000 and 5000 mg/kg of body weight for 48 hour and 14 days. Histopathological examination of fraction treated groups showed lesion of hepatic cells. Based on the result of this research, the researcher conclude that LD50 of aqueous fraction of Impatiens balsamina L was greater than 5000 mg/kg of body weight, which is classified as mild toxic.